The Influence of Culture on Entrepreneurial Intentions Among University Students. A Case Study of Uganda Christian University - Mary Mildred Mallinga (My University, 2024)
Entrepreneurship is increasingly recognized as a key driver of economic growth and innovation, with cultural factors playing a significant role in shaping entrepreneurial intentions (Hofstede, 1980; Shane, 1993). Despite this, the specific influence of cultural dynamics on entrepreneurship, particularly in diverse environments, remains underexplored. The research presented in the dissertation explores the influence of cultural dimensions on entrepreneurial intentions among university students at Uganda Christian University. The study uses the Theory of Planned Behavior (TPB) as a conceptual framework to examine how cultural variables including independence, uncertainty avoidance, power distance, and assertiveness influence students' intentions to pursue entrepreneurship. The research findings are important for understanding the relationship between cultural values and entrepreneurial behavior, particularly in the context of a university setting. The study followed a quantitative research approach, with main data collected via questionnaires issued to final-year Business Administration students. The data were evaluated with statistical methods such as mean scores, standard deviation, Pearson's correlation, and regression analysis. The findings revealed a strong entrepreneurial intent among students, with high mean scores representing their desire to participate in entrepreneurial activity. Cultural factors such as independence and assertiveness have been found to positively influence entrepreneurial ambitions, implying that students who value autonomy and are confident in their talents are more likely to view entrepreneurship as a viable career path. The study found a substantial link between cultural factors and entrepreneurial inclinations. For example, independence and assertiveness were substantially connected, indicating that students who value self-reliance are also more assertive in their business endeavours. Furthermore, uncertainty avoidance and power distance were positively connected with entrepreneurial goals, implying that students who prefer organized environments and hierarchical decision making may have significant entrepreneurial ambitions. The regression analysis confirmed these findings, indicating that cultural factors including independence, uncertainty avoidance, and power distance are strong predictors of entrepreneurial inclinations. Self-efficacy was also discovered as a moderator, strengthening the link between cultural aspects and entrepreneurial goals. The study indicated that students with high self-efficacy are more likely to overcome cultural barriers and pursue entrepreneurial activities, emphasizing the significance of confidence in one's abilities as a primary driver of entrepreneurial behaviour. Overall, the study adds to our understanding of how culture influences university students' entrepreneurial inclinations. The findings imply that cultural elements should be considered when developing entrepreneurship education programs, since they might have a considerable impact on students' inclination to engage in entrepreneurial activity. The study also emphasizes the significance of creating a supportive environment that supports independence, assertiveness and self-efficacy in order to improve entrepreneurial outcomes. Finally, the study adds to the current literature on culture and ntrepreneurship by presenting actual findings from a Ugandan university setting. The study's findings have practical consequences for legislators, educators, and university administrators who want to encourage student entrepreneurship. Future research might investigate the long-term effects of cultural characteristics on entrepreneurial behaviour, as well as cross-cultural comparisons, to gain a better understanding of how culture influences entrepreneurship in various circumstances.